Pengaruh Variasi Litologi Terhadap Kualitas Air Tanah di Daerah Semin dan Sekitarnya, Kecamatan Semin, Kabupaten Gunungkidul, Daerah Istimewa Yogyakarta - Timotius Tuska, Robert; Desie Kurnia Gae; Rean Devindra; Iqbal Hidayat; Gracia Apriyani Naibobe; Reditya Galang Pamungkas; Febri Anggara; Erlandi, Muhammad; rizqi, al hussein flowers (ReTII, 2025)
The research area is located in the physiography of the southern mountainous zone, precisely in the Semin area, Semin District, Gunungkidul Regency, Special Region of Yogyakarta is an area composed of two formations, namely the Oyo formation and the Semilir Formation which are composed of different rock units and have different rock compositions. The methods used in the study were TDS (Total Dissolve Solid), DHL (Electrical Conductivity), pH, and MAT (Groundwater Level). The purpose of this study is to determine the influence of lithology on groundwater quality and to find out groundwater that is suitable for consumption by the community. The pattern of groundwater flow to the elevation of MAT is more westward. The TDS value shows that the groundwater at the research site is classified as freshwater and has passed the groundwater quality test. EC values range from 209 – 1104 μs/cm. Groundwater pH testing ranges from 6.9 – 7.5. In the study area, there are predominantly carbonate sedimentary rocks, namely calcarenite 82.6% and clastic sediments, namely breccia 4.3%, and pyroclastic rocks, namely tuff 13.1%. Groundwater quality in the three types of lithology found to be suitable for consumption because it has not passed the water quality threshold. However, there is one well in lithology that has a slightly cloudy, smelly, and tasteful color, this well water is suspected to be polluted. Keyword : Springs, Hydrogeology, Semin